The effectiveness of learning strategies such as summary writing, schemas and conceptual mapping asaids for the teaching of reading to first year students of the B. A. program and the technical career in english at Centro Regional Universitario de Veraguas - García A., Milagro del C.
The research was undertaken in response to the dificulties yhat the students attending the School of English had, un both programs, the Licenciatura or Bachelor program in English and the technician with special tranng in English, at the time they need t oread for comprehension qhen taking the literatura couses, they also need t oread for understanding when they study for the test that they had to take in other suvjets More specifically, the students who enter the two careers offered by the School of English usually lack cognitive learning strategies even in theirs mother tongue, this fact makes it more dificult for hem t oread comprehensively in the second language. This reseacrh intends to present additional strategies to be incorporated to the Reading and writing class, in order to prepare first year students of the School if English to become betther readers.